PS01.206: ASSESSMENT OF THE GASTRIC CONDUIT RECONSTRUCTION USING INDOCYANINE GREEN FLUORESCENT IMAGING DURING ESOPHAGECTOMY. (14th September 2018) - Yamabuki, Takumi; Ohara, Masanori; Kaneko, Tsukasa; Fujiwara, Aki; Takahashi, Ryou; Komuro, Kazuteru; Iwashiro, Nozomu
Abstract: Background: Recently, indocyanine green (ICG) fluorescent imaging has been applied as a real-time navigation tool in various surgical fields. We used ICG fluorescent imaging for gastric conduit reconstruction during esophagectomy. Methods: A total of 92 consecutive patients with esophageal cancer who received gastric conduit reconstruction during esophagectomy from February 2011 to December 2017 were enrolled in the present study. We made gastric conduit with hand-assisted laparoscopic surgery (HALS) following esophagectomy. A gastric conduit with a width of 3cm was usually fashioned. After evaluation of the blood flow to the gastric conduit using ICG fluorescent imaging, anastomosis was done by circular stapler. Results: The study group was comprised of 73 males and 19 females and the median age was 70 years (range 54–85 years). Nineteen patients received preoperative chemotherapy and eleven patients received preoperative chemo-radiotherapy. Forty-eight patients underwent thoracoscopic esophagectomy, nineteen patients underwent thoracotomy and twenty-five patients underwent laparoscope assisted transhiatal esophagectomy. In eighty-five patients, reconstruction was done via the posterior mediastinal route, while six patients ware treated by the retrosternal route, and the subcutaneous route was used in one patient. Cervical anastomosis was done in 84 patients and intrathoracic anastomosis was done in eight patients. The complications of the gastric conduit reconstruction were anastomotic leakage in one (1.1%) patient and stricture of the anastomosis site requiring esophageal dilatation in 26 (28.3%) patients. Periodic esophageal dilatation was done in 13 (14.1%) patients. There was one case of stricture of the gastric conduit, one case of bleeding of the gastric conduit and one case of fistula between the gastric conduit and the lung. Conclusion: The gastric conduit reconstruction using ICG fluorescent imaging during esophagectomy may contribute to a reduction in the incidence of anastomotic leakage. However, further advancement of the relevant skills is required to improve the incidence of stricture of the anastomosis site. Disclosure: All authors have declared no conflicts of interest.